Evaluation of Electronic-based Population Administration Services Policy at the Population and Civil Registration Office of Bengkulu City - Indarti, Sri; Andriadi, Mardoni; Rosidin, Rosidin (GAYAKU PUBLISHER, 2024)
The electronic-based population administration service policy has been developed as a service innovation related to Bengkuly City population and Civil Registration Service. The Population administration service policy is implemented through the Electronic Based Citizen Administration Service System (SLAWE) application. The aim of this research is to determine the evaluation of electronic-based population administration service policies at the Bengkulu City Population and Civil Registration Service. The method used in this research is a qualitative method with a descriptive approach. The theory used in this research is William N. Dunn's policy evaluation theory with indicators of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. The results of the research show that the implementation of the electronic-based population administration service policy has not gone completely well. Based on the results of observations, researchers still found several problems experienced, such as network interference which could cause system errors. Apart from that, there is limited time in providing services through the Slawe application where service recipients can only access the Slawe application only during working hours. Outside of working hours they cannot provide services, resulting in a less than optimal process in providing population administration services by Population and Registration Service employees. Bengkulu City Civil Service to people who use the Slawe application.